ANALISIS BUDAYA HOFSTEDE: KESENANGAN VS PENGEKANGAN TERHADAP KUALITAS LAYANAN PADA SEKTOR PARIWISATA BALI - Agustina, Ni Ketut Wiwiek (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2025)
This study explores the interplay between Hofstede’s cultural dimension of Indulgence versus Restraint and service quality in the tourism sector, with a focus on Bali’s hospitality industry. While prior research has extensively examined Hofstede’s cultural dimensions such as Power Distance and Individualism-Collectivism, this article addresses a critical gap by analyzing the understudied dimension of Indulgence-Restraint and its implications for service encounters. Utilizing the SERVQUAL framework—which measures service quality through reliability, responsiveness, tangibles, assurance, and empathy—the study investigates how cultural programming influences interactions between service providers (hosts) and tourists (guests). Findings reveal that Bali’s service sector, characterized by Restraint (marked by strict social norms, lower subjective well-being, and disciplined work ethics), delivers high-quality services that align with the expectations of indulgent Western tourists, who prioritize leisure and personal gratification. Despite cultural contrasts, the restrained cultural traits of Balinese hosts, including adherence to moral discipline and focus on responsibility, contribute to positive service evaluations, fostering tourist loyalty. This research underscores the nuanced role of cultural dimensions in shaping service quality perceptions and highlights the adaptive strategies of restrained cultures in global tourism. The study advocates for culturally informed service management practices and suggests future longitudinal analyses to further dissect the dynamics of cross-cultural service encounters.